EXPLORING EFL LEARNER`S VOCABULARY LEARNING STRATEGIES AT DARUSSALAM ISLAMIC ISTITUTES - Marifatun Najiyah; Langgeng Budianto; Mutmainnah Mustofa (Graduate Program, University of Islam Malang, 2022)
EFL students should have vocabulary mastery as basic unit toÂ support the understanding of the English learning process. This study is focused on several aims Those are to find out the features of vocabulary learning strategies, to find the most strategy which is used by efl learners, and to know the least common vocabulary learning strategy which is made by EFLÂ Darussalam Islamic Institute. The study was carried out to 61 students as samples to collecting data.Â The majority of the respondent consist of 53 female respondents and 8 male respondents. The data collection involved observation, questionnaire, and interview instruments. Afterward, main instrument is a set of questionnaires which was adapted on Schmittâ€˜s (1997) taxonomy; determination strategy (DET), social strategy (SOC), memory strategy (MEM), cognitive strategy (COG), and metacoginitive strategy (MET). The 33 questions are adapted. The overall implication of vocabulary learning strategies indicated that the most strategy applied is a cognitive strategy which is preferably used strategy by EFL learners with the highest total average score among others 3.27. And the least vocabulary learning strategy used is social strategies with the lowest total average scores 2.81 And the features shown by the respondents are they tend to use a mechanical means.Â Keywords: â€œLanguage Learning Strategy (LLS)â€, â€œVocabulary learning strategies (VLSs)â€, â€œEFL studentsâ€.